2022
DOI: 10.3390/genes13030479
|View full text |Cite
|
Sign up to set email alerts
|

Does the Expression and Epigenetics of Genes Involved in Monogenic Forms of Parkinson’s Disease Influence Sporadic Forms?

Abstract: Parkinson’s disease (PD) is a disorder characterized by a triad of motor symptoms (akinesia, rigidity, resting tremor) related to loss of dopaminergic neurons mainly in the Substantia nigra pars compacta. Diagnosis is often made after a substantial loss of neurons has already occurred, and while dopamine replacement therapies improve symptoms, they do not modify the course of the disease. Although some biological mechanisms involved in the disease have been identified, such as oxidative stress and accumulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 155 publications
(207 reference statements)
0
4
0
Order By: Relevance
“…The latter can alter gene expression by causing epigenetic changes, such as DNA methylation, and the post-translational modification of histones and non-coding RNAs (ncRNAs, the most studied of which are microRNAs or miRNAs). The regulation of genes responsible for monogenic forms of PD may also be involved in sporadic PD [ 19 ].…”
Section: Familial and Sporadic Forms Of Pd Epigenetic Aspectsmentioning
confidence: 99%
“…The latter can alter gene expression by causing epigenetic changes, such as DNA methylation, and the post-translational modification of histones and non-coding RNAs (ncRNAs, the most studied of which are microRNAs or miRNAs). The regulation of genes responsible for monogenic forms of PD may also be involved in sporadic PD [ 19 ].…”
Section: Familial and Sporadic Forms Of Pd Epigenetic Aspectsmentioning
confidence: 99%
“…Recent studies have shown that methylation of the SNCA gene (the gene coding for α-synuclein) may be involved in disease via structural changes or overexpression of the protein, leading to protein aggregation, or via impaired gene expression. 4 It is reported that there is a reduced SNCA gene methylation in the substantia nigra in patients with PD as well as PARK16/Iq32, GPNMB aberrant gene methylation in PD patients postmortem. The current knowledge of various epigenetic mechanisms and their role in regulation of transcriptional and translational machinery have hinted toward a vast arena that still needs to be explored to completely understand the processes involved in neurodevelopment as well as manifestation of neurodevelopmental disorders.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Further, most of the studies evaluating the role of epigenetics in pathogenesis have focused on the analysis of promoter methylation of causative Parkinson’s disease (PD) genes in post-mortem brains and peripheral blood. Recent studies have shown that methylation of the SNCA gene (the gene coding for α-synuclein) may be involved in disease via structural changes or overexpression of the protein, leading to protein aggregation, or via impaired gene expression . It is reported that there is a reduced SNCA gene methylation in the substantia nigra in patients with PD as well as PARK16/Iq32, GPNMB aberrant gene methylation in PD patients post-mortem.…”
Section: Introductionmentioning
confidence: 99%
“…The regulation of genes responsible for monogenic forms of PD may be involved in sporadic PD. Lanoré et al [ 9 ] reviewed the epigenetic mechanisms regulating gene expression, including DNA methylation, histone modification and epigenetic changes by non-coding RNAs. An example is SNCA , encoding α-Synuclein, with the understanding of its regulation being a longstanding central focus for the community working on PD.…”
mentioning
confidence: 99%